Demonetization and Financial Inclusion in the Indian Context: Examining the Impact of Demonetization on Financial Inclusion in the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Financial Inclusion plays a pivotal role in the process of advancement and the sustainable development of any country. This paper deals with the concept of demonetization and financial inclusion in the Indian context because the issue of financial inclusion and demonetization in India becomes a challenge for the economy of India. In this paper, the researchers tries to presents the position of financial inclusion in India and initiatives taken by RBI and government and also study the importance of demonetization as a measure of financial inclusion. The data used for this research work in mainly based on secondary data. The secondary data are collected from various magazines, books, journals, articles, RBI reports and documents related to financial inclusion and demonetization. It can be concluded that financial inclusion is an important approach to remove poverty and for inclusive growth. The study also concluded that demonetization has encouraging impact on equivalent financial system; it has led to enhance financial inclusion.